Sustainable Intensification of Feed Value Chains in Mixed Crop-Livestock Systems: Towards Improved Forages for Small Ruminants. A Preliminary Report - Kemaw, Biruk; Dereje, Eden; Ekule, Muluken; Wamatu, Jane (2024)
This report aims to explore the varieties and production methods of improved forage, identify key stakeholders in the value chain, and examine the significant challenges and opportunities present in developing a forage value chain targeting small ruminants. It provides an overview of improved forage production throughout the value chain in North Shewa Zone in Ethiopia.